2017
DOI: 10.1002/2017jb014284
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the crust and uppermost mantle in the northern Canadian Cordillera from receiver functions

Abstract: The northern Canadian Cordillera (NCC) is an active orogenic belt in northwestern Canada characterized by deformed autochtonous and allochtonous structures that were emplaced in successive episodes of convergence since the Late Cretaceous. Seismicity and crustal deformation are concentrated along corridors located far (>200 to ~800 km) from the convergent plate margin. Proposed geodynamic models require information on crust and mantle structure and strain history, which are poorly constrained. We calculate rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 56 publications
(94 reference statements)
4
28
0
Order By: Relevance
“…Major faults acting as terrane boundaries are shown as dashed vertical black lines with major geologic features identified at the top of each cross section. The continental Moho picks from four studies are projected onto our cross‐section results and shown as orange squares (IRIS DMC, ), green diamonds (Allam et al, ), gray triangles (Tarayoun et al, ), and red circles (Miller et al, ). The continental Moho model generated from a nonperturbational linear surface wave only inversion (Haney et al, ) is shown as red lines in the cross sections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Major faults acting as terrane boundaries are shown as dashed vertical black lines with major geologic features identified at the top of each cross section. The continental Moho picks from four studies are projected onto our cross‐section results and shown as orange squares (IRIS DMC, ), green diamonds (Allam et al, ), gray triangles (Tarayoun et al, ), and red circles (Miller et al, ). The continental Moho model generated from a nonperturbational linear surface wave only inversion (Haney et al, ) is shown as red lines in the cross sections.…”
Section: Resultsmentioning
confidence: 99%
“…Thick fore arc (e.g., Cook Inlet) and intermontane (e.g., Copper River) basins with highelevation transpressional (e.g., Alaska Range) and arc volcanic (e.g., Wrangell Volcanic Field) peaks provide evidence of both the complex terrane assembly and active subduction zone tectonics. Aside from the basin signatures (e.g., Cook Inlet, Susitna, and Copper River), the middle-to-upper crust is faster to the south and (Allam et al, 2017), gray triangles (Tarayoun et al, 2017), and red circles (Miller et al, 2018). The continental Moho model generated from a nonperturbational linear surface wave only inversion (Haney et al, 2016) is shown as red lines in the cross sections.…”
Section: Wrangellia Composite Terranementioning
confidence: 99%
“…These data represent P ‐to‐ S converted ( Ps ) or back‐scattered ( Pps and Pss ) waves from discontinuities in seismic velocities in the subsurface and are sensitive to scale lengths of 1 to 10 km. A recent study used receiver functions to characterize the architecture of the crust and uppermost mantle within the NCC, although at low spatial resolution (~200‐km station spacing; Tarayoun et al, ). These results indicated a relatively shallow (~32 ± 2 km) Moho characterized by a downward increase in seismic velocity, consistent with previous studies (Clowes et al, ; Hammer & Clowes, ).…”
Section: Receiver Function Imagingmentioning
confidence: 99%
“…These results indicated a relatively shallow (~32 ± 2 km) Moho characterized by a downward increase in seismic velocity, consistent with previous studies (Clowes et al, ; Hammer & Clowes, ). Immediately below the Moho, receiver functions resolved a deeper seismic discontinuity characterized by a downward decrease in seismic velocity, which was loosely interpreted as the LAB (Tarayoun et al, ). Unfortunately, these inferences were based on the presumed lateral continuity of the velocity contrast observed on a single receiver function phase ( Ps ), which may be contaminated by shallower structure and suffer from poor spatial sampling.…”
Section: Receiver Function Imagingmentioning
confidence: 99%
“…Previous studies conducted in Alberta consistently reported the existence of azimuthal anisotropy in western Canada at lithospheric depths: The upper‐mantle anisotropy is mostly aligned along an NE‐SW orientation according to SKS splitting measurements from teleseismic arrivals, which is roughly parallel to the direction of absolute plate motion (Courtier et al, ; Saruwatari et al, ; Shragge et al, ; Wu et al, ). Crustal anisotropy, on the other hand, is usually stress‐ (Crampin, ; Gavin & Lumley, ) or structure‐induced (Licciardi et al, ; Meadows & Winterstein, ), especially in the upper crust (Balfour et al, ; Tarayoun et al, ). At local scales, anisotropy can result from the preferential opening of microscale, fluid‐filled fractures under the maximum horizontal compressive stress (Crampin, ; Kaneshima et al, ) and deformation‐induced, crystal‐preferred orientation along preexisting faults or folds (Eken et al, ; Licciardi et al, ).…”
Section: Introductionmentioning
confidence: 99%